Health-Related Quality of Life in Obese Presurgery Patients with and without Binge Eating Disorder, and Subdiagnostic Binge Eating Disorders - Rita Marie Sandberg; Jens K. Dahl; Einar Vedul-Kjelsås; Bjørnar Engum; Bård Kulseng; Ronald Mårvik; Lasse Eriksen (Journal of Obesity)
Objective. To study health-related quality of life (HRQoL) in obese presurgery patients with binge eating disorder (BED) and with subdiagnostic binge eating disorder (SBED) compared to patients without eating disorders or SBED. Method. Participants were patients referred to St. Olavs University Hospital, Norway, for bariatric surgery. Eating Disorders in Obesity (EDO) questionnaire was used to diagnose BED and SBED. Short-Form Health Survey (SF-12) assessed health-related quality of life. Questionnaires were returned by 160 of 209 patients. The present study sample consisted of 143 patients (103 women and 40 men) as 17 patients did not complete the SF-12. Results. Patients with BED and patients with SBED both had significantly lower mental HRQoL, but not physical HRQoL, compared to patients without eating disorders. Discussion. The findings indicate that obese presurgery patients with BED, and also SBED, may have special treatment needs in regard to their mental health.